Characteristic of Orangutan Habitat in Coal Mining Rehabilition Area in East Kalimantan, Indonesia - Liza Niningsih; Hadi Sukadi Alikodra; Sri Suci Utami Atmoko; Yeni Aryati Mulyani (Institut Pertanian Bogor (IPB University), 2017)
The majority of wild orangutans are found outside of the protected areas, including in coal mining areas which generally overlapping with orangutan habitat. Thereby, mining ensured a direct impact on orangutans. Opportunities orangutans to survive in the mining area depends on various factors, one of them is the ability of orangutan to adapt to habitat change. We investigated habitat characteristics in the coal mining area consist of land cover types, species composition, and the structure of vegetation. Data were collected from April to September 2014 in the coal mining rehabilitation area (CMRA) of PT KPC in East Kutai. Mining caused the natural habitat fragmented into smaller patches in the form of CMRA and natural forests remaining. The forest stand in CMRA compiled by the small trees of the same species and age class. It caused the canopy is not always continue. Food trees and nest trees were limited in CMRA. Exotic species dominated in CMRA, namely: Senna siamea, Falcataria moluccana, and Senna surattensis. CMRA is not the good habitat for orangutan if seen from the aspect of either structure or vegetation composition. The quality of habitat can be improved by modifying the structure and vegetation composition, build the ecosystem corridors, increase public awareness, and involve various stakeholders at the landscape level.